Nutrition at a Glance : The Democratic Republic of Congo - World Bank (Washington, DC, 2014)
Democratic Republic (DR) of Congo has higher rates of stunting than its immediate neighbors in the Africa region. Other countries with similar per capita incomes such as Somalia and Liberia exhibit lower rates of child stunting, which demonstrates the ability to achieve better nutrition outcomes despite low income. Under nutrition is not just a problem of poverty. Children are undernourished in 26 percent of even the richest households. This is typically not an issue of food access, but of caring practices and disease. Vitamin and mineral deficiencies impact well-being, and are pervasive in the DR Congo. The World Bank is supporting a US$150 million Health Sector Service Rehabilitation Project which intends to ensure that target populations receive a well-defined package of quality essential health services.